Robotic-assisted interval cytoreductive surgery in ovarian cancer: a feasibility study - Semiramis L. Carbajal-Mamani; David Schweer; Merry J. Markham; Ashwini K. Esnakula; Joseph R. Grajo; Jacqueline C. Castagno; Joel Cardenas-Goicoechea (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveThe primary objective was to assess the feasibility of robotic-assisted interval cytoreductive surgery for achieving complete cytoreduction for patients with advanced-stage ovarian cancer. The secondary objective was to examine the perioperative outcomes.MethodsA retrospective study of 12 patients with stage IIIC or IV ovarian, fallopian tube, and primary peritoneal carcinoma who underwent interval cytoreductive surgery after neo-adjuvant chemotherapy.ResultsOptimal cytoreduction was achieved in 100% of selected patients. Complete cytoreductive surgery was achieved in 75% of patients. The estimated mean blood loss was 100 mL. The median length of hospital stay was 2 days. Perioperative complication and 30-day readmission rates were 8.3% (1 patient). The median follow-up time was 9.5 months.ConclusionRobotic-assisted interval cytoreductive surgery in ovarian cancer is safe and feasible and may be an alternative to standard laparotomy in selected patients.